Discrete mathematics - Johnsonbaugh, Richard 1941- (Pearson Education Limited, 2019)
"An accessible introduction to the topics of discrete math, this best-selling text also works to expand students' mathematical maturity. With nearly 4,500 exercises, Discrete Mathematics provides ample opportunities for students to practice, apply, and demonstrate conceptual understanding. Exercise sets features a large number of applications, especially applications to computer science. The almost 650 worked examples provide ready reference for students as they work. A strong emphasis on the interplay among the various topics serves to reinforce understanding. The text models various problem-solving techniques in detail, then provides opportunity to practice these techniques. The text also builds mathematical maturity by emphasizing how to read and write proofs. Many proofs are illustrated with annotated figures and/or motivated by special Discussion sections. The side margins of the text now include "tiny URLs" that direct students to relevant applications, extensions, and computer programs on the textbook website."